Centrocestus formosanus (Opisthorchiida Heterophyidae) como causa de muerte de alevines de tilapia gris Oreochromis niloticus (Perciforme Cichlidae) en el Pacífico seco de Costa Rica - León Alán, Dennis (2010)
Centrocestus formosanus (Opisthorchiida: Heterophyidae) as a cause of death in gray tilapia fry Oreochromis niloticus (Perciforme: Cichlidae) in the dry Pacific of Costa Rica. Centrocestus formosanus is a zoonotic trematode from Asia and has been mainly associated as cause of death of cultured fish. To identify pathogen trematode species in tilapia fry (Oreochromis niloticus) and to determine mollusks hosting these parasites, freshwater mollusks were collected from tilapia cultured ponds and experimental infections were carried out with tilapia fries and different mollusk species. A total of 907 freshwater mollusks were obtained from tilapia ponds and were identified to species level, four gastropods and one bivalve were determined: Melania tuberculata, Melanoides turricula, Pomacea flagellata, Haitia cubensis and Anodontiles luteola. For the first time, the presence of M. turricula and H. cubensis are reported in Costa Rica. Seven morphotypes of cercariae (Xifiodiocercaria, Equinostoma, Oftalmocercaria, Parapleurolofocercus, Cistocerca, Furcocercaria and Leptocercaria) parasitizing all five species of mollusks were found, all of distome type. Experimental exposure of tilapia fry to M. tuberculata demonstrated that the parapleurolofocercus morphotype found in the mollusk is in accordance with the finding of C. formosanus in tilapia fry. An abundance and mean intensity of 1018-1027 digeneans per gill in each exposed fish was determined. Centrocestus formosanus is reported for the first time in Costa Rica, for which the primary and secondary intermediate hosts were also determined.